THE EFFECTIVENESS OF SILENT WAY IN IMPROVING STUDENT LINGUISTIC PERFORMANCE IN INTENSIVE ENGLISH COURSE (IEC) CLASS - pathul indriana (SOLID, 2019)
Abstrak –this classroom research answers the two questions in the research problems. Firstly, Silent Way Method is so effective in improving student linguistic performance in Intensive English Course at Year 2 students in the Department of English Education Program at the Faculty of Teachers Training and Education as it explores students speaking skill to emerge and those who are shy feel confident to speak English even a bit. Secondly, it is so clear that Silent Way Method gives evidence to us that it can significantly improved student linguistic performance in Intensive English Course at Year 2 students in the Department of English Education Program at the Faculty of Teachers Training and Education by looking at the evidence as follows: 1)Teacher can provide oral fluency practice using presentation and group work model, 2) Teacher succeeds very well in achieving direct error correction  and the discourse is allowed to proceed with minimum  interruption, 3) In giving content  feedback, teacher suceeds to create an atmosphere which is conducive to learning and is likely to promote learner involvement, 4) By constantly checking  for  confirmation, it creates considerable evidence that teachers who constantly  seek clarification, check  for confirmation and who do not always accept the first contribution a student offers are more likely to maximize linguistic performace potential than those who do not constantly, 5) Teacher succeeds in engaging students and  in  promoting  longer verbal communication. His verbal behaviour allows students to play a full and active role in classroom, producing more  complete, more natural responses, 6) Teacher only intervenes when necessary, giving language support, correcting  errors or adding a personal comment, 7) As far as the learner contributions are concerned, it is evident from this extract that learners and teacher are actively engaged in constructing a piece of discourse which resembles a conversation. Silent Way Method indeed has a number of  positive  effects, from  an  excited, questioning approach to teaching to improved classroom interaction and involvement with the students. By controlled use of language and by matching pedagogic and linguistic goals, teacher facilitates and promotes reformulation and clarification, leading to greater involvement and precision of language on the part of the  learners.